Research of High Precision Harmonic Drive with Short Flexspline of Heliostat in Solar Thermal Power - Guanghui Yin; Lü Hongzhan (Jixie chuandong)
Heliostat transmission system of solar power tower requires high precision but conventional transmission can’t meet such precision. A harmonic drive with short flexspline is developed， which makes full use of the advantages of high precision of harmonic drive and combines the characteristics of zero teeth difference type output mechanism and harmonic drive. Based on statistics and probability theory， transmission error is calculated and the sensitivity of error of parts is analyzed with the Monte Carlo method. The results show that the transmission precision can meet the requirements of the heliostat and the flexible wheel and the output rigid wheel have the greatest influence on the transmission precision. Meanwhile， the developed harmonic drive device has smaller length to diameter ratio than the traditional harmonic drive and it realizes the miniaturization of its volume.